Strong rotated cube textures in thin cold-rolled potassium-doped tungsten sheets during annealing up to 1300 °C. Issue 1 (March 2021) - Tarras Madsen, D; Ciucani, U M; Hoffmann, A; Pantleon, W
Abstract: Due to the high operation temperatures, microstructural changes will occur in tungsten when used as plasma-facing material in future fusion reactors. In drawn tungsten wires, potassium doping has proven to prevent such undesired changes effectively. This strategy has been adapted to thin cold-rolled tungsten sheets containing 80 ppm potassium. Their texture evolution during annealing is investigated using electron backscatter diffraction. In the as-rolled condition, a strong cube texture is present with a volume fraction of 67.0 % deviating maximal 15° from the rotated cube orientation. This texture intensifies strongly during isochronal annealing for 2 h at temperatures between 1000 °C and 1300 °C; the higher the temperature, the higher the rotated cube fraction. The volume fraction of 94.8 % obtained after 2 h at 1300 °C does not change significantly during further annealing. These are remarkably strong textures for a body-centered cubic metal compared e.g. to commonly reported high volume fractions of 30 % for Goss orientations in silicon steels. Reliable quantification of such strong texture components requires analysis of orientations individually.